In Vitro Release Ability of Nanoparticles Poly-Lactic-Co-Glycolic-Acid (PLGA) Gel Containing Pegagan Leaves Ethanolic Extract (Centella asiatica L.) - Mardiyanto; Elsa Fitria Apriani; Pandu Kalingga Jati (Universitas Airlangga, 2023)
Background: Pegagan (Centella asiatica L.) leaves are proven to contain high concentrations of flavonoid compounds as antioxidants. Flavonoids are unstable compounds due to environmental influences such as light, humidity, pH, and oxygen. The stability of pegagan extract was proven to be improved by making the extract into nanoparticle preparations. Objective: This study aims to formulate nanoparticles of pegagan into gel preparations and determine their release ability with the Franz diffusion test using a cellophane membrane compared to pegagan gel not formulated into nanoparticles. Methods: Nanoparticles were made using poly-lactic-co-glycolic acid polymers and then formulated into gels with various concentrations of Carbopol 934, namely 1, 1.5 and 2%. The gel nanoparticles were then subjected to the characterization of the preparation, stability test and release test of the preparation. Results: A concentration of 1% Carbopol 934 provides the best evaluation of gel preparations where the gel produced was homogeneous, pH was around 6.2, viscosity was 3417.12 cPs, spreadability was 5.1 cm, and adhesion was 209.33 seconds. The stability test showed no significant organoleptic and pH changes (p>0.05). The release kinetics model occurs at zero order. F1 has a higher reaction kinetics constant (k) than the other formulations, so drug release occurs faster. Conclusion: The best formula of pegagan (F1) nanoparticle gel was proven to have good physical stability and release ability.